Antiquity in the history of music: A critical review of the music textbooks for secondary education in Spain. (May 2023) - Martínez-Rodríguez, Marta
The history of music is shaped through narratives that sometimes contain a number of issues regarding cultural stereotypes, historiographic approaches, Eurocentrism or colonialism. For this reason, its transmission and the way it is taught must be the object of study and careful consideration. The present research analyses – on the basis of narratological and organological premises – the contents that shape the discourses underlying the coverage of the ancient period by music education textbooks used in the Spanish compulsory secondary education stage. To this effect, an ad hoc instrument was designed and implemented on 24 coursebooks. The results confirmed that the chronological narrative is the most widely used strategy and that in more than half of the textbooks under examination the history of music begins to be told after Antiquity. Other findings were that the construct of the 'foundational' civilisations of the West is still perpetuated and that an organological narrative is proposed which is inspired by a diffusionist approach. In conclusion, we detect patterns that are controversial and need to be subjected to revision at a time when educational textbooks are a decisive resource that adapts the official curriculum and mediates between the latter and music education teachers.